Web application for logic design - Tam, Jean San (2015)
Computer-based instruction is an educational programme in which students interact with a computer as a main element of the learning process. It is considered a more effective alternative compared to traditional teaching method. The purpose of this project aims to furnish a better learning style by using interactive tool such as web application. The web application was created to support Logic design, which is the fundamental concept underpinning all modern computer systems. Understanding logic design can help to make complex decision making in programs. However, it is crucial to understand the basic concepts such as truth table, logic equation or Karnaugh map. Covering the basic concepts will be the scope of this web application. To keep the web application more interactive and engaging, JavaScript was implemented to provide a more dynamic experience. In addition, it is supported by most web browsers including mobile browsers. After the application is implemented, a user acceptance test was conducted by 20 students to test for acceptability of the application. Lastly, the application achieved the desired purpose to serve all students a functional learning web application.